Environmental Priorities and Poverty Reduction : A Country Environmental Analysis for Colombia - Sánchez-Triana, Ernesto; Ahmed, Kulsum; Awe, Yewande (Washington, DC: World Bank, 2012)
The analysis of the cost of environmental degradation conducted as part of the country environmental analysis (CEA) shows that the most costly problems associated with environmental degradation are urban and indoor air pollution; inadequate water supply, sanitation, and hygiene; natural disasters (such as flooding and landslides); and land degradation. The burden of these costs falls most heavily on vulnerable segments of the population. To address these problems, this report identifies a number of cost-effective policy interventions that could be adopted in the short and medium terms to support sustainable development goals. In recent decades, considerable progress has been made in addressing the water and the forestry environmental agendas. The impact of environmental degradation on the most vulnerable groups suggests the need to increase emphasis on environmental health issues. However, the environmental management agenda has yet to catch up with this shift in priorities from watershed and forestry to environmental health problems because mechanisms in the current institutional structure to signal these changes are not yet in place. Improved monitoring and dissemination of information on environmental outcomes, assignment of accountability for environmental actions and outcomes, and involvement of a broad range of stakeholders are three important mechanisms to allow these signals to be picked up.